"Governor of the House of Pancake": A content analysis of the political framing of Chris Christie's size in online news media. Issue 1 (2nd January 2017) - Bresnahan, Mary; Zhuang, Jie; Anderson, Jennifer; Zhu, Yi; Viken, Gregory
ABSTRACT: New Jersey governor and presidential candidate Chris Christie exemplifies the epitome of stigma against fatness in a political candidate. Since Christie became newsworthy several years ago, political journalists, other political candidates, cartoonists, comedians, and social commentators often have satirized his weight. In order to investigate the extent of political weight stigma, a content analysis was conducted of 319 online news stories about Chris Christie between 2011 and 2014 identifying 1, 490 fat references from political commentators and the public. Over 80% of the 1, 490 comments were stigmatizing references to his weight. The most common expression of stigma was negative attribution about Christie's character associated with large size followed by unflattering metaphors to describe Christie. In every case where political commentators made stigmatizing weight comments, numerous stigmatizing weight comments were posted by the public. This result poses a question for responsible political journalism and stigmatizing public framing of weight and ableism.